2015
DOI: 10.1016/j.jacc.2015.09.063
|View full text |Cite
|
Sign up to set email alerts
|

Durability of Treatment Effect Using a Drug-Coated Balloon for Femoropopliteal Lesions

Abstract: The 24-month outcomes from the trial demonstrate a durable and superior treatment effect of DCB versus PTA with significantly higher primary patency, lower CD-TLR, and similar functional status improvement with fewer repeat interventions. (Randomized Trial of IN.PACT Admiral Drug Eluting Balloon vs Standard PTA for the Treatment of SFA and Proximal Popliteal Arterial Disease [INPACT SFA I]; NCT01175850; and IN.PACT Admiral Drug-Coated Balloon vs. Standard Balloon Angioplasty for the Treatment of Superficial Fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
232
1
6

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 342 publications
(252 citation statements)
references
References 29 publications
8
232
1
6
Order By: Relevance
“…[4][5][6] In addition to improved efficacy in terms of improvement of symptoms, time free from reintervention, and reductions in amputation rates, studies have also shown that the procedures have similar levels of safety, which is understandable considering the similar techniques employed.…”
Section: Discussionmentioning
confidence: 99%
“…[4][5][6] In addition to improved efficacy in terms of improvement of symptoms, time free from reintervention, and reductions in amputation rates, studies have also shown that the procedures have similar levels of safety, which is understandable considering the similar techniques employed.…”
Section: Discussionmentioning
confidence: 99%
“…The rates of clinically directed target vessel revascularization (CD-TLR) were 9.1% and 28.3% (p < 0.001) for the DCB and PTA groups, respectively. The rate of vessel thrombosis was low (1.5% DCB vs. 3.8% PTA; p = 0.243), with no new events reported between 1 and 2 years [11]. The use of drug-coated balloons on the venous circulation has also been studied.…”
Section: Discussionmentioning
confidence: 99%
“…Beyond striking surgical arterial reconstructions [76][77][78][79], new tapered nitinol [81], drug-eluting stents (DES) [82], and original drugeluting balloon, (DEB) [83] were imagined. Novel or redesigned directional or rotational atherectomy devices [84], together with latest "bioresorbable scaffolds" technologies [85], represent few additional of numerous achievements that challenge today ancient technical barriers [1,29,75,[81][82][83][84][85][86].…”
Section: Contemporary Landmarks In Ischemic Wounds Revascularizationmentioning
confidence: 99%
“…Beyond high-performance techniques in reconstructing arterial flow [72][73][74][75][76][77][78][79][80][81][82][83][84][85][86], new strategies about "when" and "where" to perform appropriate revascularization emerge today [1,27,30,35]. Contemporary practitioners equally avail key data on the molecular mechanisms generating ischemic threat and tissue regeneration [59][60][61].…”
Section: New Strategies For "Wound Targeted Revascularization"mentioning
confidence: 99%